Medical Statistics : a Guide to Data Analysis and Critical Appraisal. - Peat, Jennifer (John Wiley & Sons, 2008)
Holistic approach to understanding medical statistics. This hands-on guide is much more than a basic medical statistics introduction. It equips you with the statistical tools required for evidence-based clinical research. Each chapter provides a clear step-by-step guide to each statistical test with practical instructions on how to generate and interpret the numbers, and present the results as scientific tables or graphs. Showing you how to:.:.; analyse data with the help of data set examples (Click here to download datasets).; select the correct statistics and report results for publication o.